2023
DOI: 10.3389/fpubh.2023.1167515
|View full text |Cite
|
Sign up to set email alerts
|

Sociodemographic and behavioral factors associated with controlled hypertension after 9 years of observation of a PURE Poland cohort study

Abstract: IntroductionDespite some improvement in awareness and treatment of hypertension, blood pressure control is still below expectations in Poland. The aim of the study was to analyze the secular trend of hypertension prevalence in the PURE Poland cohort study over 9 years of observation and to analyze factors associated with controlled HT.MethodsThe study group consisted of 1,598 participants enrolled in a Prospective Urban and Rural Epidemiological Study (PURE), who participated both in baseline (2007–2010) and 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 35 publications
0
0
0
Order By: Relevance
“…The results of a recent study of the Polish PURE cohort showed there was a 3.5% decrease in current smokers during the analysed period (from 20.2% at the baseline study to 16.7% in the 9-year follow-up) [23], an increase in the prevalence of diabetes from 17.7% at baseline to 28.3% at 6-year follow-up [35]. They also showed a 16.5% increase in the prevalence of arterial hypertension at the 9-year follow-up (from 69.4% at baseline to 85.9% at 9-year follow-up) [31]. In addition, they showed min.…”
Section: Impact Of the Studymentioning
confidence: 92%
See 1 more Smart Citation
“…The results of a recent study of the Polish PURE cohort showed there was a 3.5% decrease in current smokers during the analysed period (from 20.2% at the baseline study to 16.7% in the 9-year follow-up) [23], an increase in the prevalence of diabetes from 17.7% at baseline to 28.3% at 6-year follow-up [35]. They also showed a 16.5% increase in the prevalence of arterial hypertension at the 9-year follow-up (from 69.4% at baseline to 85.9% at 9-year follow-up) [31]. In addition, they showed min.…”
Section: Impact Of the Studymentioning
confidence: 92%
“…The main research directions in the analyses of the data collected in the Polish PURE cohort during the longterm follow-up period focused on dietary factors [8][9][10][11][12][13][14][15][16], the effect of CETP and PLTP protein activity on lipid disorders [17,18], overweight and obesity [19][20][21][22], atti- tudes toward tobacco smoking [23][24][25][26], alcohol consumption [27], sleep [28], quality of life [29], prevalence and determinants of hypertension [30,31], and carbohydrate metabolism disorders [32][33][34][35][36].…”
Section: Impact Of the Studymentioning
confidence: 99%